Paulo Freire’s contributions to the Countryside Education: teacher training and Science teaching (Práxis Educativa, 2021)
This work presents a reflection on the theoretical and methodological thinking of the Brazilian educator Paulo Freire in the field of the Countryside Education and his contributions to the process of training teachers of Natural Sciences. With this objective, the Pre-service teacher education courses of the Countryside Education at the Federal University of Paraná - Coastal Sector was taken as a reference, from which the historical, philosophical, social and practical principles and influences that led to the implantation of courses of this nature at national public universities are presented. Methodologically, it is a theoretical study, but it also has empirical evidence of educational practices already carried out. Among the final reflections, the importance of Freire’s pedagogy stands out as a counter-hegemonic and guiding pedagogy for the education of the people from the rural areas, waters and forests.Keywords: Freirean thinking. Training of countryside teachers. Scientific education.